2014
DOI: 10.3390/ma7096796
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Aluminum Foam-Filled Thin-Wall Steel Tube by Friction Welding and Its Compression Properties

Abstract: Aluminum foam has received considerable attention in various fields and is expected to be used as an engineering material owing to its high energy absorption properties and light weight. To improve the mechanical properties of aluminum foam, combining it with dense tubes, such as aluminum foam-filled tubes, was considered necessary. In this study, an aluminum foam-filled steel tube, which consisted of ADC12 aluminum foam and a thin-wall steel tube, was successfully fabricated by friction welding. It was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…TiH 2 powder (<45 µm) was used as the blowing agent. The amount of TiH 2 was one mass% relative to the mass of ADC12 burrs in accordance with reference [13]. As shown in Figure 2b, the mixture was placed in a SUS304 stainless-steel tube fixed by a steel jig.…”
Section: Fabrication Of Al Foam-filled Steel Tubementioning
confidence: 90%
See 1 more Smart Citation
“…TiH 2 powder (<45 µm) was used as the blowing agent. The amount of TiH 2 was one mass% relative to the mass of ADC12 burrs in accordance with reference [13]. As shown in Figure 2b, the mixture was placed in a SUS304 stainless-steel tube fixed by a steel jig.…”
Section: Fabrication Of Al Foam-filled Steel Tubementioning
confidence: 90%
“…Friction stir back extrusion (FSBE) has been developed for coating wear-resistant Al-25%Si on the surface of an Al-Si-Cu alloy AC2B engine cylinder [10], and for fabricating Al tubes and copper tubes with a fine grain structure from bulk starting materials [11,12]. Hangai et al developed a fabrication process for Al foam-filled steel tubes [13,14] and Al foam-filled Al tubes [15,16] by FSBE. In this process, a bulk Al precursor was placed into a metal tube; then a rotating tool was plunged onto the precursor.…”
Section: Introductionmentioning
confidence: 99%
“…All previous studies have indicated that the interaction between the foam and the tube improves the deformation behaviour of the structure and results in a high energy absorption of FFTs both under quasi-static [7,[10][11][12][13][14] and dynamic loading conditions [15,16]. However, Sirinath et al observed that an aluminium foam filled steel tube has a lower specific energy absorption when compared to an empty tube [7].…”
Section: Introductionmentioning
confidence: 91%
“…FSP is also successful in the manufacture of foam filled tubes. Investigation of Al foam/Al tube [19], Al foam/steel [20] tube has demonstrated a strong bond of the precursor to the interior of the tube. Although, foaming of precursors as a result of frictional heating has been proved to be a viable option [21], the extraction of the foam, however, can be a problem.…”
Section: Introductionmentioning
confidence: 99%